2017
DOI: 10.1007/s10584-016-1829-4
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐scale intercomparison of climate change impacts simulated by regional and global hydrological models in eleven large river basins

Abstract: Ideally, the results from models operating at different scales should agree in trend direction and magnitude of impacts under climate change. However, this implies that the sensitivity to climate variability and climate change is comparable for impact models designed for either scale. In this study, we compare hydrological changes simulated by 9 global and 9 regional hydrological models (HM) for 11 large river basins in all continents under reference and scenario conditions. The foci are on model validation ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
117
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(131 citation statements)
references
References 41 publications
4
117
0
1
Order By: Relevance
“…The ability of HMs to represent hydrological changes is an important issue that is often neglected in climate change impact assessments and how this should be done is not agreed upon in the scientific community (e.g. Hatterman et al 2016, Merz et al 2011. Refsgaard et al (2013) and Coron et al (2011) suggest how this could be done for catchment-scale impact modelling but these methods are difficult to implement in continental-or globalscale models.…”
Section: Uncertainties and Limitationsmentioning
confidence: 99%
“…The ability of HMs to represent hydrological changes is an important issue that is often neglected in climate change impact assessments and how this should be done is not agreed upon in the scientific community (e.g. Hatterman et al 2016, Merz et al 2011. Refsgaard et al (2013) and Coron et al (2011) suggest how this could be done for catchment-scale impact modelling but these methods are difficult to implement in continental-or globalscale models.…”
Section: Uncertainties and Limitationsmentioning
confidence: 99%
“…We excluded the Nile River from the investigation because its discharge was considerably overestimated. It is frequently reported that GHMs substantially overestimate the river discharge of the Nile River (e.g., Haddeland et al, 2011;Hattermann et al, 2017). This poor performance for the Nile River by H08 was attributed not only to the model's formulation but also to the reliability of meteorological data in the basin, which has been commonly seen in other GHMs.…”
Section: Validation At Selected Basinsmentioning
confidence: 98%
“…Although the key hydrological processes were represented, the land surface hydrology and river routing sub-models of H08 are relatively simple (Appendix A). Moreover, the hydrological parameters were not tuned to individual basins, which yielded a generally lower reproducibility of historical river flow observations (e.g., Hattermann et al, 2017). In cases in which the H08 model was applied to specific basins, sensitivity testing and hydrological parameter calibration were conducted systematically using reliable long-term observations (e.g., Hanasaki et al, 2014;Masood et al, 2015).…”
Section: Potential Sources Of Uncertaintymentioning
confidence: 99%
“…In the context of the present study we are not able to identify the exact reasons why model performance is hindered in some basins. It is unrealistic for a global LSM to achieve top performance around the world (Hattermann et al, 2017), as, due to its global nature, some fixes in some regions could result in deteriorations in performance in other parts of the land surface. Thus, the interpretation of the following analysis of the present study should consider the model deficiencies revealed in this section.…”
Section: Model Evaluationmentioning
confidence: 99%
“…These variables have traditionally been prioritized for bias correction as they are considered the most important driving variables of hydrological processes in modelling applications -even though from a physical perspective radiation is the driving force of the hydrological cycle. However, many state-of-the-art regional and global hydrological models (GHMs) and land surface models (LSMs) require -apart from precipitation and temperature -additional meteorological forcing, such as solar radiation, air humidity, surface air pressure, and wind speed (a summary of the input variables needed by various hydrological models can be found in the Supplement of Hattermann et al, 2017). For this reason, biases in variables like radiation, humidity, and wind speed can hinder the representation of hydrological fluxes such as runoff, evapotranspiration (ET), snow accumulation, and snowmelt by the impact models (Hagemann et al, 2011;Haddeland et al, 2012), indicating that bias correction should be extended to include more input variables.…”
Section: Introductionmentioning
confidence: 99%